Monetary policy risk-taking transmission channel: A case of banking industry in Kenya - David Ndwiga (Kenya Bankers Association (KBA), 2024)
Using a Panel VAR model and annual bank level data for the period 2008-2022, this study investigated banks risk taking behaviour amid monetary policy tightening considering the role of banks' non-interest-bearing deposits and equity levels. Estimation results found monetary policy tightening and equity levels reduces the bank risk taking behavior thus evidence of monetary policy risk-taking transmission channel. However, the contrary was reported with regard to bank liability: - non - interest bearing deposit "pseudo assets". However, interaction between policy rate, equity and "pseudo assets" was found to increase bank risk appetite significantly. This study is important since under the risk-taking channel view, a change in the policy rate is immediately transmitted to money-market instruments of different maturity and to other short-term rates, such as interbank deposits and this quickly affects the interest rates that banks charge their customers for variable-rate loans, including overdrafts.
Keywords: 330; Risikopräferenz; Bank; Geldpolitik; Geldpolitische Transmission; Kenia